Sacrificial gelatin microspheres for tissue engineering applications - Leong, Wenyan (2016)
Tissue engineering, or the development of three-dimensional (3D) macroscopic biological tissues in vitro, have various important applications: as a medical intervention to replace lost or abnormal cells, tissues and organs through transplantation, as a self-regulating drug delivery vehicle, or as an in vitro study model or drug testing platform. The technology is highly anticipated to resolve the severe donor shortage and immune rejection issues of current replacement therapy: allogenic and xenogeneic transplantations. Furthermore, successful development of in vitro study and testing models not only decreases the use of animal models which pose deviation from human responses; it also can increase drug safety by providing crucial insights on drug dosing prior to pre- and clinical trials. However, oxygen diffusion constraints poses a bottleneck in development of macroscopic tissues constructs. We therefore propose to incorporate sacrificial gelatin microspheres in macroscopic hydrogel scaffolds as a versatile tissue engineering platform through two purposes, namely as a porogen for better permeability, and additionally as a cell delivery vehicle for non-anchorage dependent cell (non-ADC) types. Gelatin, being a temperature-responsive hydrogel, dissolves naturally when constructs are cultured for tissue development at physiological temperature; this is a simple and natural one-step strategy of creating cavities in a macroscopic construct.